Identifying drivers of change in bryophyte and lichen species occupancy in Scotland. (June 2022) - Pakeman, Robin J.; O'Brien, David; Genney, David; Brooker, Rob W
Highlights: Attributing biodiversity trends is necessary to take corrective action. We link trends in bryophyte and lichen occupancy to indicator values. Climate change, pollution and increased shade shifted species occupancy patterns. Contrasting trends imply increased bryophytes competitive advantage over lichens. Prevailing negative trends for lichens are concerning for Scottish biodiversity. Abstract: The attribution of biodiversity trends to the action of individual drivers is a first step in developing strategies to conserve, enhance and restore that diversity. One approach to that identification is to link information on species trends with information on ecological preferences that relate to the drivers. Long-term and short-term occupancy trends for 326 bryophyte species (1972–2015 and 2005–2015, respectively) and 437 lichen species (1971–2015 and 2005–2015, respectively) for Scotland were linked with appropriate indicators to assess the action of specific drivers. Bryophyte species of heathlands and woodlands showed positive trends, whilst lichen species from these habitats showed negative trends. Bryophytes and lichens of drier habitats and locations tended to have more positive trends whilst those of wetter habitats tended to be negative. Similarly, evidence suggested that bryophytes and lichens of open areas had more negative trends than those of shadier habitats and that species from both groups of higher fertility habitats had more positive trends than those of less fertile ones. Bryophyte species from warmer areas tended to increase in range. Opposite trends for bryophytes and lichens in heathlands and woodlands suggest competition for space or opposite reactions to other drivers, but it is clear that they should not be lumped into a single functional grouping. There were clear trends for suggesting that increased temperatures (bryophytes only), cumulative nitrogen pollution and reduced land use intensity were shifting assemblages. The overall predominance of negative trends for lichens suggests that many species have lost habitat through decreasing light availability and increased dryness, and potentially through competition with bryophytes. Given the international importance of Scotland for both these groups, these trends for lichens are of concern.